Gambaran Konsumsi Mie Instan dan Kejadian Overweight Remaja di SMKN 1 Kota Jambi - Putri, Rizka Amanda; Wulansari, Arnati; Jeki, Andicha Gustra; Indrawati, iin (Prosiding Seminar Kesehatan Nasional, 2024)
Instant noodles are a type of junk food often consumed by adolescents. Junk food is a type of food that contains a lot of fat. This situation will eventually lead to overweight-obesity. Overweight is a definition of a condition in which the body has a lot of fat deposits. The purpose of this study was to describe the consumption pattern of instant noodles and the incidence of overweight among students of SMKN 1 Jambi City. This study is a quantitative study using cross-sectional method. This research was conducted in March- July 2024. The population in this study were students of SMK N 1 Jambi City who were in grades X and XI as many as 1,224 students with a sample of 87 people. This research instrument used the SQ-FFQ questionnaire and anthropometric measurements of nutritional status with the IMT/U Z-score indicator. The sample in this study was taken using a proportional random sampling technique. Data analysis was univariate. The results showed that 80.5% of the respondents consumed instant noodles frequently and 44.8% of the respondents were overweight. As an input for students and students of SMKN 1 Jambi City, which is expected to further increase awareness of the importance of paying attention to a good and healthy diet to be consumed.